Analytical aspects of protein carbonyl group in oxidized canine serum. (International Journal of Health, Animal Science and Food Safety, 2016)
Oxidative stress (OS) is an imbalance between oxidants and anti-oxidants and plays an important rolein the aetiology and/or the progression of several diseases. Protein carbonyl (PCO) groups are so farused as biomarkers of OS in humans (Colombo et al, 2015).The aim of our study was to investigate whether PCOs are present in canine serum and if they can bemeasured spectrophotometrically using a method not yet validated in dogs.The presence of PCO was investigated by Western blotting after separation by SDS-PAGE of serum atdifferent dilutions (either before or after oxidation with 10% cigarette smoke extract). Protein labellingwith 2,4-Dinitrophenylhydrazine (DNPH, Brady's reagent) was followed by a two-steps incubation withprimary anti-dinitrophenyl-KLH antibodies (rabbit IgG fraction) and secondary goat anti-rabbit IgG, HRPconjugate. Signal was developed with Enhanced Chemiolumionescence (ECL).Serum PCO were quantified using a commercially available assay (Protein Carbonyl Content Assay Kit -Abcam, UK), based on derivatization of proteins with 1,4-dinitrophenylhydrazine (DNPH) andsubsequent formation of protein-conjugated dinitrophenylhydrazones (DNPs) with a peak absorbanceat 366 nm.Western blot showed an evident band of apparent MW of 69 kDa, consistent with carbonylated dogserum albumin. The spectrophotometric assay failed to demonstrate any signal at 366 nm using themanufacturer’s instructions or modified protocols.This study demonstrated that PCO are present in oxidized canine serum. However, thespectrophotometric assay employed in this study is not enough sensitive to detect PCOs. Furtherstudies are needed to assess whether this depends on the poor re-solubilisation of DNPs, or on the lowconcentration of PCOs in dogs.
Keywords: Dog; Western blotting; carbonyl group proteins; oxidative stress; oxidants